2015
DOI: 10.4012/dmj.2015-067
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical surface modifications to titanium implants using the tresyl chlorideactivated method

Abstract: Tresyl chloride (2,2,2-trifluoroethanesulfonyl chloride)-activated method is an easy and simple method for immobilizing biological molecules onto a titanium surface. Tresyl chloride was directly dropped onto a titanium surface without any solvent. Tresylated titanium disks were immersed in a protein or peptide solution to give protein-or peptide-immobilized titanium. Frontier molecular orbital calculations suggested that tresylation of the OH compound improved its reactivity towards the amine groups of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…This result confirms the reported ability of FN to facilitate early osteoblast adhesion and differentiation and agrees with previous observations in vitro on human and murine osteoblast-like cells, and in vivo after positioning of FN-modified dental titanium implants in dogs [ 66 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…This result confirms the reported ability of FN to facilitate early osteoblast adhesion and differentiation and agrees with previous observations in vitro on human and murine osteoblast-like cells, and in vivo after positioning of FN-modified dental titanium implants in dogs [ 66 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, ALP activity was crucial for the mineralization and also indicative for the maturation of the osteoblasts 50) . Hayakawa et al also reported change in ALP activity of MC3T3-E1 cells cultured on fibronectin-immobilized Ti surface after 3, 15, and 52 days 7) .…”
Section: Discussionmentioning
confidence: 89%
“…Histatin-1, JH8194, and mixed histatin-1 with JH8194 peptides at ratio 1:1 were reconstituted as the manufacturer's advice. Tresylated Ti disks were immersed in 10 µM peptides solution at 37°C for 1 day 7) . Ti disks were washed twice with phosphate buffered saline (PBS) and used for entire experiments.…”
Section: Immobilization Of Histatin-derived Peptides By Tresyl Chloride Activation Technique and Surfaces Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Aung et al grafted an allylamine and fibronectin composite surface onto zirconia and reported that the fibronectin grafted surface significantly stimulated the bioactivity of osteoblast-like cells 11) . Hayakawa et al developed a new method for immobilizing proteins or cytokines onto titanium, called the tresyl chloride-activated method 12) . Better bone response has been reported by immobilizing TGF-β2 or fibronectin onto titanium by the tresyl chloride-activated method 13,14) .…”
Section: Introductionmentioning
confidence: 99%